Impaired Neurocognitive Performance and Mortality in HIV: Assessing the Prognostic Value of the HIV-Dementia Scale. - Banerjee, Nikhil; McIntosh, Roger C.; Ironson, Gail (AIDS & Behavior, 2019)
This study examined whether global HIV-associated neurocognitive impairment (NCI), assessed with the HIV-Dementia Scale (HDS), predicted mortality in an ethnically diverse sample of 209 HIV-positive adults. Participants were predominantly in the mid-range of illness at baseline, and followed over 13-years. At baseline, 31 (15%) participants scored in the NCI range (HDS ≤ 10); 58 (28%) died during follow-up. Baseline NCI was significantly associated with earlier mortality (HR = 2.10, 95% CI [1.10–4.00]) independent of sociodemographic and HIV disease-related covariates. Less errors on the antisaccade task, an index of executive/attention control, was the only HDS subtest predicting earlier mortality (HR = 0.72, 95% CI [0.58–0.90]). In the absence of an AIDS-defining condition, NCI, particularly in the executive/attention domain, is an independent prognostic marker of mortality in a diverse HIV-positive cohort. These findings highlight the clinical utility of brief cognitive screening measures in this population.